Camu-camu: Historical rescue as a basis for its valorization in the Amazon - Andrade, Jerusa Souza; Andrade, Diva Souza (Seven Editora, 2023)
The camu-camu is a fruit native to the Amazon, rich in ascorbic acid and antioxidant substances. Aiming to contribute to the knowledge of the food potential of the Amazon and to the rescue of the work of pioneering researchers, this work aimed to raise information about the camu-camu for its appreciation in the Amazon, considering until the early 1990s. This work discussed the botanical description and taxonomic position, synonymy and common names, geographical distribution and dispersal, habitat and edapho-climatic conditions, phenology and genetic variability, production and commercialization, and also the uses and technological aspects. The information promotes a historical rescue that can serve as a basis for its appreciation in the Amazon. DOI: https://doi.org/10.56238/alookdevelopv1-136